Panorama of teaching on older adults or aging in undergraduate nutrition programs at Brazilian Higher Education Institutions - Renata Breda Martins; Claus Dieter Stobäus; Carla Helena Augustin Schwanke (Brazilian Society of Geriatrics and Gerontology, 2022)
Objective: This study aimed to present an overview of teaching about older adults or aging in undergraduate nutrition programs of higher education institutions (HEIs) in Brazil. Methods: This is a cross-sectional study with data obtained from HEI websites in 2018. Results: Most of the 527 analyzed HEIs were private institutions (88.05%). Courses related to older adults/aging were offered by 63.98% of the HEIs; 58.04% included shared content (not only involving older adults), 76.15% were offered from the fifth to the eighth semester, 53.19% were theoretical, 61.51% had a workload ≥ 60 hours/semester, and 92.16% were mandatory pedagogical activities. Internships involving older adults (one or more) were observed only in 4.65% of the programs. Conclusions: Approximately one-third of Brazilian HEIs do not offer courses on older adults or aging in their undergraduate nutrition programs. However, population aging, with its inherent demands, is a reality in Brazil and in the world. Further studies are suggested to expand the reflection and contribute to a more qualified training of nutritionists for the care of older adults.